Using median rule in determining the establishment of service station between Al hasaka and Al kamishly serian cities - الرحيم, صلاح; كاظم, عبد المنعم (Journal of Economics and Administrative Sciences, 2013)
Research indicates that the second half of the twentieth century marked large interests in the service industry by government and private organizations in that one, and the service industry has become the bedrock of plans in achieving economic and social development. From this standpoint felt specialists and researchers the importance of transport modes, including rail, which should be available between Almnltq Civil populated as services organized by the competent authorities to achieve the active participation of citizens in economic and social development in the region and that the term services means economic activities, which are the results Pollack concrete such as accepting the situation and satisfaction them or satisfaction through these and other findings, which eventually form the interests Pollack concrete and that have achieved some of the privileges and benefits to student need, and is the subject of this research on the problem of providing transport services better for travelers by train between the cities of Hasaka and Qamishli Alsorretan, where there is a railway line (train) between the two cities mentioned, but was not taken into consideration the number of villages and populated areas between them, and there is no stop between the two cities, which caused the problem of not ease the transition, and to develop stop new train has been applied base mediator in determining plant construction train passenger service in the light of information related to population in villages located between the two cities above that number (59) village where they were to obtain research data from the records of the Department of Statistics Hasakah province of Syria.